Konsepsi dan Praksis Belajar dalam Dunia Pendidikan - Entoh Tohani (LPPM Press, 2013)
This article try to explain conception of learning in educational process. It is important to explorethe conception in order to get good understanding of the meaning which is useful for teachers and othereducators, hopefully they could be good teachers, e.g. they can do teaching learning proses well byapplication the right concept of learning. As known, there are many cases in our education system whichdescribes problems on achieving quality of human resources especially low spirit of learning in ourcountry which must be overcome.